Theory and numerical modelling of parity-time symmetric structures in photonics: introduction and grating structures in one dimension - Phang, Sendy; Benson, Trevor M.; Susanto, Hadi; Creagh, Stephen C.; Gradoni, Gabriele; Sewell, Phillip D.; Vukovic, Ana (Springer Nature, 2017)
A class of structures based on PT PT-symmetric Bragg gratings in the presence of both gain and loss is studied. The basic concepts and properties of parity and time reversal in one-dimensional structures that possess idealised material properties are given. The impact of realistic material properties on the behaviour of these devices is then investigated. Further extension to include material non-linearity is used to study an innovative all-optical memory device.